A comparison of ionospheric TEC between the South Atlantic anomaly region and the Indian Ocean region based on TIEGCM simulations in 2002 - Li, Zheng; Wang, Yan; Shao, Jingjing; Wang, Luyao; Li, Jingyuan; Zhang, Hua; Xu, Xiaojun; Gu, Chunli (Frontiers in Physics, 2024)
Using the Thermosphere-Ionosphere-Electrodynamic General Circulation Model (TIEGCM), a comparison of the ionospheric total electron content (TEC) between the South Atlantic anomaly (SAA) and the Indian Ocean (IO) at solar maximum is performed in this study. The results show that the average TEC in the SAA is greater than that in the IO in general. In order to further analyze the difference between the two regions, the empirical orthogonal function (EOF) are used to investigate the temporal and spatial characteristics of TEC. The EOF method separate part of the global four-peak structure (an equatorial ionization anomaly structure, distributed in Southeast Asia, South America, Africa, and central Pacific) and spatial variations in both regions. Moreover, the first mode of EOF shows the different distribution of EIA in South America and central Pacific caused by deviation of geomagnetic field and tides between two regions, and the enhancement of TEC in SAA region at dusk is emphasized, but the enhancement of TEC in IO region at dawn is emphasized. The second mode performs the distribution of EIA in Africa related to solar radiation and × drift.The third mode indicates the similar spatiotemporal variations from the geomagnetic field. Besides, the correlation between TEC and Dst in two regions indicate that there are some deficiencies in simulation to the specificity of SAA, and the deficiencies are likely caused by the model's inaccurate simulation of the magnetic field and particle deposition in the SAA region.The ionosphere is greatly affected by solar EUV radiation and geomagnetic activity, and shows many spatiotemporal variations, such as latitudinal variations, seasonal variations, diurnal variations, South Atlantic anomaly (SAA) and Weddell Sea anomaly (WSA) (Forbes et al., 2000). The ionosphere plays an important role in space weather, and there is a strong coupling process between it and the upper and lower regions. At high altitudes, the particle in ionosphere interacts with plasma in